2014
DOI: 10.1177/0284185113495834
|View full text |Cite
|
Sign up to set email alerts
|

Thin-section CT findings in peripheral lung cancer of 3 cm or smaller: are there any characteristic features for predicting tumor histology or do they depend only on tumor size?

Abstract: Air bronchogram on thin-section CT is characteristic feature of solid adenocarcinoma of the lung. However, other thin-section CT findings are irrelevant to tumor histology and related only to tumor size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…Similarly, spiculation is also more commonly seen in MIA (9.1%) and IAC (13.5%) lesions, compared with AIS (0%). These findings are consistent with previous studies showing that lobulation, spiculation and pleural tag are more prevalent in more advanced lung cancers (21). Air bronchogram on thin-section CT is thought to be a characteristic feature of solid adenocarcinoma of the lung.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, spiculation is also more commonly seen in MIA (9.1%) and IAC (13.5%) lesions, compared with AIS (0%). These findings are consistent with previous studies showing that lobulation, spiculation and pleural tag are more prevalent in more advanced lung cancers (21). Air bronchogram on thin-section CT is thought to be a characteristic feature of solid adenocarcinoma of the lung.…”
Section: Discussionsupporting
confidence: 93%
“…Pleural indentation is a characteristic indicating a higher likelihood of malignancy not only for subsolid nodules [ 27 ], but also for solid nodules [ 28 30 ]. An air bronchogram is also useful for differentiating lung adenocarcinoma from benign solid nodules [ 4 , 31 ] and for predicting negative nodal involvement in solid lung cancer [ 32 ], whereas the interlobular septum is useful for differentiating intrapulmonary lymph nodes [ 33 ]. In the present study, the CT findings of pleural indentation, air bronchograms, and interlobular septa received higher scores on the U-HRCT images than on the C-HRCT images.…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al [ 13 ] showed that the frequencies of lymph node metastasis and vessel invasion in adenocarcinomas with GGO components of more than 50% were significantly lower than those in adenocarcinomas with GGO components of less than 10% obtained by thin-section CT findings. There have also been studies focusing on the relationship between CT morphologic characteristics as well as tumor size and TNM grade [ 14 - 17 ]. Bajard et al [ 18 ] showed that clinical T classification was significant for the development of brain metastasis in a cohort of 305 NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%